Design of step-graded AlGaN buffers for GaN-on-Si heterostructures grown by MOCVD. (1st April 2023) - Ghosh, Saptarsi; Hinz, Alexander M; Frentrup, Martin; Alam, Saiful; Wallis, David J; Oliver, Rachel A
Abstract: For the growth of low-defect crack-free GaN heterostructures on large-area silicon substrates, compositional grading of AlGaN is a widely adapted buffer technique to restrict the propagation of lattice-mismatch induced defects and balance the thermal expansion mismatch-induced tensile stress. So far, a consolidation of the design strategy of such step-graded buffers has been impaired by the incomplete understanding of the effect of individual buffer design parameters on the mechanical and microstructural properties of the epilayers. Herein, we have analyzed a series of metal-organic chemical vapor deposition grown GaN/graded-AlGaN/AlN/Si heterostructures through in situ curvature measurements and post-growth x-ray diffraction (XRD). Our results reveal that in such epi structures, the GaN layer itself induces more compressive stress than the AlGaN buffer, but the underlying AlGaN layers dictate the magnitude of this stress. Furthermore, for a fixed AlGaN buffer thickness, the mean-stress accumulated during the GaN growth is found to be correlated with its structural properties. Specifically, one µ m thick GaN layers that acquire 1.50 GPa or higher compressive mean-stress are seen to possess 20 2 ˉ 1 XRD ω -FWHM values less than 650 arc-sec. Also, the evolution of instantaneous stresses during the growth of the AlGaN layers is found to be a valuable indicator for buffer optimization, and composition difference between successive layers is established as a crucial criterion. The results also show that increasing the total buffer thickness (for a fixed number of steps) or increasing the number of steps (for a fixed total buffer thickness) may not always be beneficial. Irrespective of the buffer thickness, optimized high electron mobility transistor structures show similarly low sheet-resistance (∼350 Ω □) −1 and high mobility (∼2000 cm 2 V −1 s −1 ) at room temperature.